KEDUDUKAN ‘URF DALAM HUKUM ISLAM - Fariqoini, Azimatul; Aini, Siti Maryam Qurotul (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2023)
In general, 'urf or custom is practiced by all fiqh scholars, especially among the Hanafi and Maliki scholars. Maliki scholars use 'urf or the traditions prevalent among the people of Madinah as a basis for establishing laws and prioritize it over isolated hadiths. Shafi'i scholars often employ 'urf in matters where the legal provisions are not explicitly defined in Sharia or in language usage. The reason scholars accept and utilize 'urf is based on a hadith narrated by Abdullah ibn Mas'ud, as reported by Imam Ahmad in his Musnad, which states: